Pemberdayaan UMKM Peyek Layyunda Desa Ngrimbi Melalui Digital Marketing - Satria Ardhana (BADAN PENERBIT STIEPARI PRESS, 2023)
UMKM is the Layyunda Project which is located in Ngrimbi Village, Bareng District, Jombang Regency. UMKM Peanut Layyunda is an MSME that is engaged in making Peanut, Shrimp and Anchovy Projects. The UMKM Peyek Layyunda was founded in Jombang in 2019 with the owner, Mrs. Datis Safarotin. The brand